2002
DOI: 10.1080/02699200210126523
|View full text |Cite
|
Sign up to set email alerts
|

'What did you say'?: understanding conversational breakdowns in children with speech and language impairments

Abstract: The study examined the types of mistakes children make during conversations with a familiar partner. The current investigation differs from previous studies because it asked what it is about the language of children with specific language impairment and phonological disorder (SLI:PD) that causes mothers to ask for clarification. Videotaped interactions were coded with the Breakdown Coding System to describe breakdowns. Not surprisingly, results indicated that children with SLI:PD were more difficult to underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 60 publications
0
14
0
5
Order By: Relevance
“…Les interactions verbales entre un adulte et un enfant souffrant de pathologie, comme la dysphasie ont également donné lieu à des recherches plus spécifiques (De Weck, 2006 ;Keith, Welsh, Camarata, Butkovsky, & Camarata, 1995 ;Vigil, Hodges, & Kle, 2005 ;Yont, Hewitt, & Miccio, 2002). Les auteurs reconnaissent principalement deux fonctions à la répétition par l'adulte de l'énoncé de l'enfant (atteint ou non d'une pathologie).…”
Section: Introductionunclassified
“…Les interactions verbales entre un adulte et un enfant souffrant de pathologie, comme la dysphasie ont également donné lieu à des recherches plus spécifiques (De Weck, 2006 ;Keith, Welsh, Camarata, Butkovsky, & Camarata, 1995 ;Vigil, Hodges, & Kle, 2005 ;Yont, Hewitt, & Miccio, 2002). Les auteurs reconnaissent principalement deux fonctions à la répétition par l'adulte de l'énoncé de l'enfant (atteint ou non d'une pathologie).…”
Section: Introductionunclassified
“…First, with regards to the frequency and source of communication breakdown, Yont et al (2002) reported that 12 children (mean age 4;1 years) with concomitant speech and language impairment experienced significantly more breakdown in communication (368 instances) than a similarly aged group of 12 typically developing peers (97 instances). Of the instances of communication breakdown, most were associated with either phonological (125) or pragmatic (112) errors by the children with concomitant speech and language impairment.…”
Section: Communication Breakdown and Repair In Children With Phonologmentioning
confidence: 99%
“…• • listeners' signals that the speakers' utterance have not been understood; and • • speakers' repairs of problematic utterances (Yont et al, 2002).…”
Section: Communication Breakdown and Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…Communication breakdowns and/or repair strategies have been studied in typically developing children (Brinton et al 1986;Gallagher 1977;Golinkoff 1986), as well as in a variety of pediatric clinical populations, including children with hearing loss (Blaylock et al 1995;Ciocci and Baran 1998;Most 2002), children with autism (Meadan et al 2006;Volden 2004), children with language impairment (Brinton et al 1988;Brinton et al 1986;Yont et al 2002), and children identified generally as having intellectual disabilities (Dacey and Kretschmer 1981;Scudder and Tremain 1992). Though communication breakdown patterns and repair strategies may be especially important aspects of pragmatic development for children with DS, the most common cause of intellectual disability (ID; Centers for Disease Control and Prevention 2006), this area has received little attention in the research literature.…”
mentioning
confidence: 99%